Towards resolving a problem of the identity of the Aethus species (Hemiptera: Heteroptera: Cydnidae) occurring in Cambodia - Lis, Jerzy A.; Lis, Barbara; Ziaja, Dariusz J.; Nakatani, Yukinobu (Zootaxa, 2014)
The genus Aethus in Cambodia is known only from a single species collected in the 1950s that was originally identified as A. indicus. However, what was regarded as A. indicus in the Oriental and Australian regions appeared to consist of three sibling species, recognizable only on the basis of male genital structures, i.e., A. philippinensis, A. pseudindicus, and true A. indicus. To date, the lack of males representing this genus from Cambodia made it impossible to verify which species actually occur in this country. The present study, based on eight males collected at the same locality in Cambodia where the specimens were originally identified as A. indicus more than 50 years ago (i.e., Siem Reap), confirmed the occurrence of A. pseudindicus, not A. indicus, as previously reported. Male genitalia, i.e. the paramere, the opening of genital capsule, and the apex of aedeagus, are described and their photographs are provided for both species.